The Development Of Salah Chair Using Electronic Sensor To Assist Disabled Muslims In Performing Prayers - Abdullah Solihin Mohd Fauzi; Ahmad Abror Hakim Sa'idan; Wan Zakiah Wan Ismail; Irneza Ismail; Mus'ab Sahrim; Bushra Naeem; Ahmad Syahmi Mohd Zain; Farah Aina Mohd Jamal; Syarfa Najihah Raisin; Juliza Jamaludin (Teknik Elektro Institut Teknologi Nasional Bandung, 2024)
Non-Indexed Publication